Femoral Diaphyseal Fractures Fixation Technique Using an Adjustable Nylon Tie in Dog (Canis lupus familiaris) and Cat (Fells catus domesticus) - Silva, Bruna Martins da [UNESP]; Charas dos Santos, Ivan Felismino [UNESP]; Doiche, Danuta Pulz [UNESP]; Picelli de Azevedo, Maria Gabriela [UNESP]; Castro Martins, David Jose de [UNESP]; Duarte Ferraz de Camargo, Barbara Wagner [UNESP]; Agostinho, Manuela [UNESP]; Ferreira, Gustavo Manea [UNESP]; Branco, Marina Paiva [UNESP]; Salewski, Gabriella Cunha [UNESP] (Univ Fed Rio Grande Do Sul, 2018)
Background: Adjustable nylon ties polyamide 6.6 is devices produced from the same material of surgical nylon wire and have been used in different surgical procedures in small animals and in human patient. Reports regarding the use of these devices as secondary fixation technique of femoral diaphyseal fractures in animals are rare in the literature. The aim of the present report case was to describe the use of adjustable nylon tie polyamide 6.6 as secondary fixation technique in a 3-year-old dog and 4-month-old cat, diagnosed with femoral diaphyseal fractures. Cases: Case I. A 3-year-old female dog was presented with reluctance to support the left hind limb, with 5 days' duration. Pain and edema on the left femoral diaphyseal region was identified. The limb was submitted to radiographic exam and revealed a closed, complete and comminuted fracture of the diaphysis of the femur, and was decided to perform a surgical stabilization by open reduction through primary fixation with intramedullary pin, and secondary fixation of bone fragments with adjustable nylon ties polyamide 6.6, as a substitute of steel cerclage wire. The bone fragments were aligmnent and fixated with five polyamide nylon ties. The excess was removed with a scalpel blade along the lock. Seven days after surgery the skin sutures were removed and were observed reluctance to support the left hind limb. Physiotherapy sessions were prescribed. Forty days after the surgery was performed a radiographic exam of the left hind limb which revealed alignment of the bone axis. Six months after the surgery, the owner reported that the dog supported the left hind limb. Case 2. A 4-month-old female cat was presented with history of trauma, with 24 h's duration, and reluctance in supporting the left hind limb. On physical examination there was identified pain on the left femoral diaphyseal region. Radiographic examination revealed a closed, complete and simple fracture of the diaphysis of the femur, and a surgical stabilization through primary fixation with intramedullary pin, and secondary fixation with three polyamide nylon ties was performed. Seven days after the surgery were observed reluctance to support the left hind limb. Three months after the surgery, the owner was contacted and he reported that the cat was supported the limb. Discussion: Adult dogs are more susceptible to diaphyseal fractures and so does the dog in the present report. On the other hand, young cats present high metaphyseal fracture rates due to the metaphyseal growth plate. However, the cat in the present report was different since it was 4-month-old and presented diaphyseal fracture. Different from steel cerclage wires, polyamide nylon ties were used as secondary fixation in diaphyseal fractures for the reason that of their stability in this kind of fracture, no tissue reaction and minimal tissue trauma. The adjustable nylon ties polyamide 6.6 were already used in different surgical procedures in human patients and animals. Complications reported in the literature due to their use were associated with erroneous surgical techniques. Adjustable nylon ties polyamide 6.6 proved to be efficient as bone cerclage device in diaphyseal multiple and simple fracture, as well as gave stability to the herein assessed adult dog and young cat, besides not inducing foreign body reactions.
Keywords: small animals; polyamide; bones; cerclage; surgery